Combining NMR of dynamic and paramagnetic molecules: fluxional high-spin Nickel(II) complexes bearing bisguanidine ligands - Roquette, Pascal; Maronna, Astrid Christine; Reinmuth, Matthias; Kaifer, Elisabeth; Enders, Markus; Himmel, Hans-Jörg (Inorganic chemistry, 2011)
A detailed nuclear magnetic resonance (NMR) study was carried out on a series of paramagnetic, tetrahedrally coordinated nickel(II) dihalide complexes featuring chelating guanidine ligands. A complete assignment of the NMR signals for all complexes was achieved by sophisticated NMR experiments, including correlation spectra. The effects of halide exchange, as well as the variation in the guanidine−metal bite angles on the paramagnetic shifts, were assessed. The paramagnetic shift was derived with the aid of the diamagnetic NMR spectra of the analogous Zn complexes, which were synthesized for this purpose. The experimentally derived paramagnetic shift was then compared with the values obtained from quantum chemical (DFT) calculations. Furthermore, variable-temperature NMR studies were recorded for all complexes. It is demonstrated that NMR spectroscopy can be applied to evaluate the rate constants of fast fluxional processes within paramagnetic and catalytically active metal complexes.
Gesehen am 20.09.2022